Awareness & attitude regarding biomedical waste disposal among post-graduate students, under-graduate students & auxiliary staff of a dental college – a questionnaire survey - Chopra, Rahul; Mathur, Shivani; Dodwad, Vidya; Sharma, Nikhil; Tevatia, Siddharth (International Journal of Dental Research, 2017)
Purpose: Indiscriminate disposal of bio medical waste poses a serious threat to environment and human health and is currently a burning issue with increasing health care facilities and associated waste generation. Hence this study assesses the awareness levels and attitude regarding biomedical waste disposal among post-graduates, under-graduates & auxiliary staff of a dental college.Materials and Method: This was a cross-sectional study conducted among post-graduates, under-graduates & auxiliary staff using a questionnaire. A total of 120 participants, 40 in each group answered the questionnaire. The answers were analyzed and graded for each group.Results: The results depict satisfactory awareness about biomedical waste disposal among post-graduates and under-graduates. However, the auxiliary staff lacks the awareness about proper biomedical waste disposal.Conclusion: The study reveals that there is a need to increase knowledge among the auxiliary staff regarding biomedical waste management by continuing training program.